Comparative iron management in hemodialysis and peritoneal dialysis patients: a systematic review - van Lieshout, Thomas S.; Klerks, Anastasia K.; Mahic, Osman; Vernooij, Robin W. M.; Eisenga, Michele F.; van Jaarsveld, Brigit C.; Abrahams, Alferso C. (Frontiers in Nephrology, 2024)
BackgroundPatients with kidney failure undergoing dialysis often suffer from anemia. Iron deficiency, along with a shortage in erythropoietin, is a common cause. Peritoneal dialysis (PD) patients may have a different iron metabolism compared to hemodialysis (HD) patients. This study aims to compare both dialysis modalities regarding their differences in iron management.MethodsPubMed (MEDLINE) and Embase were screened for randomized controlled trials and observational studies including both patients on HD or PD with information on iron management. Outcomes for iron management for this systematic review included: prevalence of supplementation, route of administration, dose, frequency and hemoglobin and iron status parameters.Results15 eligible studies (930,436 patients), of which 8 cohort and 7 cross-sectional, were analyzed. The prevalence of intravenous (IV) iron supplementation ranged from 11.7% to 84.4% in HD patients, compared to 1.6% to 49.0% in PD patients. Ten studies reported that HD patients only received IV iron, while five studies reported this for PD patients. For oral iron supplementation, three studies involved HD patients, whereas seven studies involved PD patients. The cumulative monthly IV iron dose ranged from 108 to 750 mg in the HD group, compared to 65 to 250 mg in the PD group. Hemoglobin levels ranged from 10.0 to 12.0 g/dL in HD patients, versus 9.6 to 11.9 g/dL in PD patients.ConclusionIron management differs between HD and PD patients, with HD patients receiving higher doses and more frequent IV iron. There was significant heterogeneity in the outcomes between the studies, primarily due to the lack of a uniform global policy on iron management. Despite these differences, hemoglobin levels and iron status parameters were comparable between the two groups. Future research should explore the underlying mechanisms and broader impacts of iron treatment, including patient-reported outcomes, to optimize anemia management and improve quality of life for dialysis patients.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42022336970.